Developing an Augmented Reality Chemistry Textbook on Acids and Bases with Ethnochemistry to Enhance Students Understanding of Chemical Representations - Ariani, Sunniarti; Supriadi, Supriadi; Ardiyanti, Yunita; Hidayah, Weny Amanatul; Daraswita, Adina Ayu (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
This development research presents an Augmented Reality(AR)-based textbook that integrates chemical concepts with the SASAMBO culture, highlighting an innovative approach to ethnochemistry. The study aims to produce a practical, valid, and effective AR textbook to enhance students’ understanding of chemical representations. The research follows the 4D development model: Define, Design, Develop, and Disseminate. The textbook was validated by two experts and tested for effectiveness with a limited implementation involving 26 students. Data were collected using validation and practicality questionnaires, as well as pretest-posttest evaluations. Validation data were analyzed using Aiken’s V, while improvements in students’ understanding were assessed with a paired t-test via IBM SPSS Statistics 25. Results show high validity (Aiken’s V = 0.9), strong practicality (86% average score), and a significant increase in understanding (t = 16.871, p < 0.005). These findings suggest that the AR-based textbook is a valid, practical, and effective tool for enhancing students’ comprehension of chemical representation.